Photogrammetry: An accurate and cost-effective three-dimensional ice hockey helmet fit acquisition method - Greencorn, D. J.; Aponte, D. I.; Pearsall, D. J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2018)
Ice hockey helmets must pass standardized impact tests to be certified for sale. However, these tests are performed with the helmet attached to a surrogate headform. Human head shapes are not uniform, and very few standards exist for helmet fitting for the common user. The goal of this study was to develop an accurate and cost-effective three-dimensional acquisition protocol to assess the geometric fit of human subject heads to a variety of ice hockey helmets. The study had three main objectives: First, a photogrammetry-based three-dimensional acquisition system was developed. Second, the researchers populated a database of both male human heads and ice hockey helmets by scanning five different helmet models from various manufacturers. Finally, the system accuracy and error were calculated using root mean squared errors between the dimensional difference curves of repeated scans. Errors were calculated by repeating the entire protocol error with 20 comparisons (root mean squared error = 2.83 mm), the alignment error with 5 comparisons (root mean squared error = 1.14 mm), and scaling error with 4 comparisons (root mean squared error = 1.84 mm). Suggestions are provided in the section "Discussion" on how to create a system that is more time efficient with higher resolution renders and lower error. A method that quantifies three-dimensional fit is the first step toward studying the relationship between helmet fit and user-specific helmet protection.